'Tell Me and I Forget, Teach Me and I May Remember, Involve Me and I Learn. And That's What It's About.' How a Co‐design Methodology is Used in the Delivery of Parents Building Solutions: A Qualitative Study. Issue 4 (26th November 2019) - Morris, Heather; Valentine, Cathie; Cummins, Jonathon; Dwyer, Andrea; Skouteris, Helen
Abstract : There are many parenting programs delivered in Australia and Parents Building Solutions (PBS) is one of these. Collaboratively designed by Parentzone staff of Anglicare Victoria, it has a twenty year history of building the evidence base. PBS stands apart from other programs because parents actively co‐design the sessions and content with skilled facilitators. Understanding the drivers, processes and practices that make the co‐design methodology work, is fundamental to the implementation science that underpins the program.This study aimed to examine the way co‐design was used in the delivery of PBS, specifically looking at program implementation and outcomes. Focus groups and interviews were conducted with Parentzone staff (team leaders and facilitators) and parents who had recently completed a program. Ethics approval was provided and analysis was conducted using NVivo software with co‐design as the unit of analysis. Three major themes about co‐design were present across team leaders, facilitators and parents: 1) responsiveness and flexibility are central to the functionality of co‐design within PBS; 2) facilitators implement the co‐design methodology using a suite of knowledge and skills; and 3) parents report tangible results from participating in a co‐designed parenting program. There was an overwhelming appreciation from both facilitators and parents about the co‐designed implementation style. Facilitators and team leaders highly valued the flexibility of the program which enabled their ability to respond to parent's needs. Furthermore, parents believed they achieved tangible outcomes derived from strategies and support delivered in the program. The co‐design methodology used in PBS was evident for all stakeholders and was a driver of program implementation and its outcomes. The methodology described in this has practice implications for family therapists and others who work directly parents and families.